Buddhism, Unitarianism, and the Meiji competition for universality - Mohr, Michel (Harvard East Asian monographs, 2014)
"This book spotlights the debates between Unitarianism and Buddhism in Japan since the late 1800s. Focusing on the events triggered by the missionaries of the American Unitarian Association in Japan between 1887 and 1922, this study investigates this formative time in Japanese religious and intellectual history"--Provided by publisher